Effectiveness of Intra-anal Biofeedback and Electrical Stimulation in the Treatment of Children With Refractory Monosymptomatic Nocturnal Enuresis: A Comparative Randomized Controlled Trial - Seham Mohammed Abd El-Moghny; Manal Salah El-Din; Samah Attia El Shemy (International Neurourology Journal, 2018)
Purpose To compare the effects of intra-anal biofeedback (BF) and intra-anal electrical stimulation (ES) on pelvic floor muscles (PFMs) activity, nocturnal bladder capacity, and frequency of wet night episodes in children with refractory primary monosymptomatic nocturnal enuresis (PMNE). Methods Ninety children of both sexes aged 8–12 years with refractory PMNE participated in this study. They were randomly assigned to 3 groups of equal number: control group (CON) that underwent behavioral therapy and PFM training, and 2 study groups (BF and ES) that underwent the same program in addition to intra-anal BF training and intra-anal ES, respectively. PFMs activity was assessed using electromyography, nocturnal bladder capacity was evaluated by measuring the first morning voided volume, and a nocturnal enuresis diary was used for documenting wet night episodes before treatment and after 3 months of treatment. Results After training, all groups showed statistically significant improvements in all measured outcomes compared to their pretreatment findings. The ES group showed significantly greater improvements in all measured outcomes than the CON and BF groups. Conclusions Both intra-anal BF training and ES combined with behavioral therapy and PFMs training were effective in the treatment of PMNE, with intra-anal ES being superior to BF training.